1999
DOI: 10.1164/ajrccm.160.2.9812020
|View full text |Cite
|
Sign up to set email alerts
|

CD8 + ve Cells in the Lungs of Smokers with Chronic Obstructive Pulmonary Disease

Abstract: Previous studies have shown an increased number of inflammatory cells and, in particular, CD8+ve cells in the airways of smokers with chronic obstructive pulmonary disease (COPD). In this study we investigated whether a similar inflammatory process is also present in the lungs, and particularly in lung parenchyma and pulmonary arteries. We examined surgical specimens from three groups of subjects undergoing lung resection for localized pulmonary lesions: nonsmokers (n = 8), asymptomatic smokers with normal lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
316
8
18

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 419 publications
(364 citation statements)
references
References 23 publications
19
316
8
18
Order By: Relevance
“…The numbers of macrophages and CD8+ T-cells in the bronchial mucosa and peripheral lung tissue correlate with a decline in lung function, indicating a role for these cells in the pathogenesis of COPD [2][3][4][5][6] . Studies of tissue samples from smokers and COPD patients have shown increased numbers of CD8+ T-cells in comparison to healthy control subjects, yet few studies have described the function of the these cells.…”
Section: Introductionmentioning
confidence: 99%
“…The numbers of macrophages and CD8+ T-cells in the bronchial mucosa and peripheral lung tissue correlate with a decline in lung function, indicating a role for these cells in the pathogenesis of COPD [2][3][4][5][6] . Studies of tissue samples from smokers and COPD patients have shown increased numbers of CD8+ T-cells in comparison to healthy control subjects, yet few studies have described the function of the these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Increased numbers of CD8+ T-cells, alveolar macrophages and neutrophils are characteristic pathological features of the lungs in COPD [3,4]. Eosinophil numbers are increased during exacerbations and possibly also during stable phases in a subset of patients [5].…”
mentioning
confidence: 99%
“…Eosinophil numbers are increased during exacerbations and possibly also during stable phases in a subset of patients [5]. These activated inflammatory cells can release various mediators, including leukotriene B 4 and inflammatory cytokines (e.g. Thelper cell (Th) types 1 and 2 cytokines, and tumour necrosis factor (TNF)-a) [6].…”
mentioning
confidence: 99%
“…Previous studies have shown an increased number of inflammatory cells [8,9] in pulmonary arteries from patients with COPD. Inflammatory cells are a source of cytokines and growth factors that may contribute to the development of structural and functional abnormalities of the vessel wall [23].…”
Section: Discussionmentioning
confidence: 89%
“…By contrast, at variance with primary hypertension, the medial layer of the arteries is normal or only mildly thickened [6]. These structural changes are often associated with functional impairment of the endothelium [7] and with an inflammatory process in the adventitial layer [8,9]. The mechanisms underlying the development of these structural abnormalities in pulmonary arteries are still unknown.…”
mentioning
confidence: 99%